Nongenetic causes of hypertyrosinemia that must be considered when interpreting a finding of elevated urinary tyrosine: Causas no genéticas de hipertirosinemia que deben considerarse al interpretar un hallazgo de tirosina elevada en orina - Virú-Loza, Manuel André (2023)
Mr. Editor. In several countries, newborns are screened for tyrosinemia type 1 using tyrosine as a primary marker. In some situations, elevated blood tyrosine levels are discovered due to elevated tyrosine on a urine metabolic screen. In Peru, some pediatric patients suspected of having a genetic condition (inborn error of metabolism) undergo a metabolic screening in urine that includes - among other things - the qualitative detection of tyrosine. However, when there are high levels of tyrosine in the urine this does not always mean that the patient has a genetic condition. Hypertyrosinemia is most often non-genetic in origin. Therefore, it is important to review the non-genetic causes of hypertyrosinemia and thus avoid potential misinterpretations of this finding.